2009
DOI: 10.2139/ssrn.1514165
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Catastrophic Oop Health Expenditure in India: Concepts, Determinants and Policy Implications

Abstract: The present paper attempts to modify definition of catastrophic out-of-pocket

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…36,39 Pal analyzed the data of 61 st round of National Sample Survey and showed that socially deprived classes, household size, number of children and elderly persons in house increased the probability of catastrophic spending while education level of primary and above had significant negative impact on this probability, in rural sectors. 40 The present study did not found any significant difference in probability of CHE with these factors, however, presence of an underfive member and one/more events of delivery/ miscarriage/abortion were found to have significantly increased the probability of incurring CHE. The negative value of concentration index and MDK indicated that probability of incurring CHE was disproportionately concentrated among the poor and the financing system was degressive.…”
Section: Discussioncontrasting
confidence: 81%
“…36,39 Pal analyzed the data of 61 st round of National Sample Survey and showed that socially deprived classes, household size, number of children and elderly persons in house increased the probability of catastrophic spending while education level of primary and above had significant negative impact on this probability, in rural sectors. 40 The present study did not found any significant difference in probability of CHE with these factors, however, presence of an underfive member and one/more events of delivery/ miscarriage/abortion were found to have significantly increased the probability of incurring CHE. The negative value of concentration index and MDK indicated that probability of incurring CHE was disproportionately concentrated among the poor and the financing system was degressive.…”
Section: Discussioncontrasting
confidence: 81%
“…more number of employees. This result is consistent with the studies conducted by (Pal, 2012;Hajizadeh and Nghiem, 2011;Mondal, 2010). One of the innovations of the present study (which is not observed in previous studies) was to consider the development index of the province of the place of residence of households in terms of access to healthcare providers as a factor affecting the probability of facing CHE.…”
Section: Introductionsupporting
confidence: 93%
“…Thus, only around 15% of all health expenditure in the country is borne by the state, and rest 85% comes as “out-of-pocket payment” by the people. This makes the Indian public health system grossly inadequate and under-funded[ 18 19 20 ] Moreover, only about 5.5% of the Indian population has some form of medical insurance. [ 18 ] Virtually all of the families from poor rural areas lack any form of healthcare insurance.…”
Section: Discussionmentioning
confidence: 99%